Quintuplex PCR to detect antibiotic resistance genes in Streptococcus pneumoniae / Navindra Kumari Palanisamy, Parasakthi Navaratnam and Shamala Devi Sekaran - Navindra Kumari Palanisamy; Parasakthi Navaratnam; Shamala Devi Sekaran (Faculty of Medicine, 2015)
Streptococcus pneumoniae is an important bacterial pathogen, causing respiratory infection. Penicillin resistance in S. pneumoniae is associated with alterations in the penicillin binding proteins, while resistance to macrolides is conferred either by the modification of the ribosomal target site or efflux mechanism. This study aimed to characterize S. pneumoniae and its antibiotic resistance genes using 2 sets of multiplex PCRs.